A longitudinal study of young Finnish adults’ use of subsidized, private sector dental care, 1986–1997 - Suominen-Taipale AL, Widström E (Blackwell Synergy, 2000)
Finns born after 1956 are now entitled to subsidized private sector dental care, or such persons could be enrolled in the Public Dental Service. Until 1986, eligibility was more restrictive. The purpose of this study was to investigate the use and costs of private dental care and effects of regularity of care on costs and treatment received among young Finnish adults during 1986–1997. Methods: All 1986, 1990 and 1994 recipients of reimbursement for dental care from the Social Insurance Institution were included in the study.